The Internalization of Character Education in Learning for Generation Alpha: Fostering the Emergence of Indonesia's Golden Generation 2045 - Darwati, Ida; Abidin, Yunus; Sutini, Ai (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
Generation Alpha, born in the digital era, exhibits a high dependency on technology, which poses challenges to their social and emotional development. This study examines the importance of internalizing character education in the learning process to address these challenges. Using a literature review method, this study follows a systematic approach: topic identification, data collection, classification, analysis, and conclusion. Findings indicate that integrating character education into learning enhances social and emotional skills, supporting balanced development across cognitive, psychomotor, and affective domains. This integration is crucial for shaping Indonesia’s Golden Generation 2045—individuals who are intelligent, competent, and morally grounded. However, the study is limited by its reliance on secondary sources without empirical validation. Future research should explore the practical implementation of character education and assess its long-term impact on Generation Alpha’s development.